A Case of Bilateral Conjunctivitis in a Seven-Year-Old Shih-Tzu Dog - Made Gede Adi Surya Saputra; Sri Kayati Widyastuti; Putu Ayu Sisyawati Putriningsih (Universitas Airlangga, 2024)
Background: Conjunctivitis is an inflammation of the conjunctiva that is common in dog, which also known as pink eyes. Conjunctivitis can be caused by infectious agents such as bacteria, chlamydia, and virus, and can also be induced by allergies or due to trauma. Bilateral infection may indicate they are caused by an infectious agent or allergy. Purpose: This study aims to provide veterinarians with insight into the treatment of conjunctivitis cases and the factors that hinder therapy. Case: A seven-year-old female Shih-Tzu dog has had eye problems for six months since April 2023. Physical examination revealed redness in the left and right eyes with mucopurulent exudate. Laboratory examination using an impression smear followed by cytology confirmed inflammation in the eye with many neutrophil cells and coccus-shaped bacteria. The dog was diagnosed with bacterial conjunctivitis with a good prognosis. Case Management: The therapy consisted of the administration of topical antibiotics in the form of Erlamycetin plus® (chloramphenicol and dexamethasone) eye drops for five days, followed by Erlamycetin® (chloramphenicol) eye ointment. Conclusion: After 12 days of therapy, there was no redness in the dog's eyes and only a small amount of exudate was observed. However, on day 14, the owner reported that exudates were observed in the dog's eyes. The therapy resulted in improvements but was not optimal because the owner did not consistently follow the recommendations.